Reinforce Technology IR 4.0 Implementation for Improving Safety Management in Construction Site - Kasim, Narimah; Razali, Sali Amirah (International Journal of Sustainable Construction Engineering and Technology, 2021)
Industrial Revolution 4.0 in recent years notorious for new advances in high technology, full automation, and digitalization. This technology has demanded by academic researchers and practitioners, on the construction industry sector in Malaysia. The construction industry is involved with complex management processes causes impossible to eliminate the potential hazards at the workplaces. Despite, the rate of accidents and deaths continue to increase year by year. The objectives of this research are to identify IR 4.0 implementation, drivers and barriers of IR 4.0 implementation for safety management in the construction industry. In approaching IR 4.0 technology, a systematic literature review has been applied. The paper is reviewed by extracting information based on topics and highlighting research directed to implement IR 4.0 for safety management. After further analyzed, 32 out of 80 journal papers were selected. Several ideas on IR 4.0 technologies with its drivers and barriers were highlighted in relation to safety management practices in the term of realize suitable practices, safety training, and planning give the benefits in implementation IR 4.0. This review provides insights into the areas that technology needs to focus on, enabling a tangible shift towards implementing IR 4.0 in the construction industry.